Derrida´s Challenge to History: Text and Context: Gnozeologická skepse mezi konstatováním a performací - Lavický, Jan (Dějiny – teorie – kritika, 2024)
Jacques Derrida´s deconstruction is a way of thinking that is still not very well known in Czech intellectual life and for various reasons professional historians see it as a threat to the history as a scientific discipline. In reality, as can be seen from the example of G.G. Iggers, such fears tend to be based on ignorance or irresponsible treatment of Derrida´s texts, and as a result the possible benefits of Derrida´s conceprts for history are overlooked. This study aims to elucidate the key concepts and sections of Derrida´s philosohpy, especially those that relate relatively directly to historical science and have potentially important consequences for it.